Advances in lysosomal escape mechanisms for gynecological cancer nano-therapeutics - Heng Wei; Yingying Hao; Jin Zhang; Yue Qi; Chong Feng; Chen Zhang (Journal of Pharmaceutical Analysis)
Gynecological cancers present significant treatment challenges due to drug resistance and adverse side effects. This review explores advancements in lysosomal escape mechanisms, essential for enhancing nano-therapeutic efficacy. Strategies such as pH-sensitive linkers and membrane fusion are examined, showcasing their potential to improve therapeutic outcomes in ovarian, cervical, and uterine cancers. We delve into novel materials and strategies developed to bypass the lysosomal barrier, including pH-sensitive linkers, fusogenic lipids, and nanoparticles (NPs) engineered for endosomal disruption. Mechanisms such as the proton sponge effect, where NPs induce osmotic swelling and rupture of the lysosomal membrane, and membrane fusion, which facilitates the release of therapeutic agents directly into the cytoplasm, are explored in detail. These innovations not only promise to improve therapeutic outcomes but also minimize side effects, marking a significant step forward in the treatment of ovarian, cervical, and uterine cancers. By providing a comprehensive analysis of current advancements and their implications for clinical applications, this review sheds light on the potential of lysosomal escape strategies to revolutionize gynecological cancer treatment, setting the stage for future research and development in this vital area.